2017
DOI: 10.1111/scs.12454
|View full text |Cite
|
Sign up to set email alerts
|

Family members' experiences with intensive care unit diaries when the patient does not survive

Abstract: Family members of nonsurvivors had a need to have the ICU time explained and expressed. The diary might work as a form of 'survival kit' to gain coherence and understanding; to meet their needs during the hospital stay; and, finally, to act as a bereavement support by processing the death of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 29 publications
1
52
0
15
Order By: Relevance
“…Of the 14 papers included in the review, eight papers were assessed using the AXIS appraisal tool for surveys [35][36][37][38][39][40][41][42], four were assessed using the CASP tool for qualitative studies [42][43][44][45][46], and two were assessed using the CASP tool for randomised control trials [47,48].…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 14 papers included in the review, eight papers were assessed using the AXIS appraisal tool for surveys [35][36][37][38][39][40][41][42], four were assessed using the CASP tool for qualitative studies [42][43][44][45][46], and two were assessed using the CASP tool for randomised control trials [47,48].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Study outcomes were based on experiential perceptions, in the form of narrative [43][44][45], descriptive numerical data [35,39,42], or a combination of both [46,47]. One exception was a randomised trial which reliably tested efficacy and reported treatment outcomes [48].…”
Section: Bereavement Interventions and Their Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICU diaries were offered to the relatives after patient deaths. This practice is supported by a recent study describing how family members experience diaries to support social interaction, and rational and emotional understanding, and to bridge the gap between the hospitalisation and postbereavement period (Johansson, Wahlin, Magnusson, Runeson, & Hanson, ). Complicated grief is experienced by a significant proportion of relatives after intensive care treatment and is associated with being present at the time of death, not having said goodbye, the patient refusing treatment, the patient dying when still intubated and poor communication between relatives and physicians (Kentish‐Barnes et al., ).…”
Section: Discussionmentioning
confidence: 85%
“…The ICU diaries were offered to the relatives after patient deaths. This practice is supported by a recent study describing how family members experience diaries to support social interaction, and rational and emotional understanding, and to bridge the gap between the hospitalisation and postbereavement period (Johansson, Wahlin, Magnusson, Runeson, & Hanson, 2017 , 2015). Bereavement follow-up services have been reported to be present in about one-third of the Australian and about half of the New Zealand ICUs, and while social workers conducted most of the follow-up in Australia, nurses had this responsibility in New Zealand, which was comparable to our findings from Norway (Mitchell, Coombs, & Wetzig, 2017).…”
Section: Discussionmentioning
confidence: 88%